Disparity of serum uric acid threshold for CKD among hypertensive and non-hypertensive individuals - Bowen Zhu; Fang Li; Weidong Zhang; Shuan Zhao; Nana Song; Shi Jin; Ziyan Shen; Yufei Lu; Yang Li; Hong Liu (Renal Failure)
Introduction Hypertension and rising serum uric acid (sUA) played a pivotal role in the development of Chronic Kidney Disease (CKD). This study investigates the interactive effect of sUA and hypertension on CKD and identifies the optimal threshold of sUA among individuals with and without hypertension in the Chinese community population.Materials and methods The study included 4180 individuals aged 45–85 years, derived from the China Health and Retirement Longitudinal Study (CHARLS) between 2011 and 2015. Additionally, a hospital-based study enrolled subjects in the Department of Nephrology at Zhongshan Hospital, China from January 1, 2019, to December 31, 2021. The interaction effect analysis were used to assess the impact of sUA and hypertension on CKD. We also compared the distribution of sUA and the CKD risk in community populations, distinguishing between those with and without hypertension. For the hospital-based population, kidney injury was marked by a KIM-1 positive area.Results Our results indicate a higher prevalence of CKD in the community population with hypertension (10.2% vs. 3.9%, p < .001). A significant additive synergistic effects of the sUA and hypertension on the CKD risk were found. When the sUA level was < 4.55 mg/dL in the hypertensive population and < 5.58 mg/dL in the non-hypertensive population, the risk of CKD was comparable (p = .809). In the propensity score matched (PSM) population, the result remained roughly constant.Conclusion Therefore, even moderate levels of sUA was associated with a higher risk of CKD in middle-aged hypertensive patients, who warrant stricter sUA control.